Experimental Investigation on the CO2 Two-phase Ejector with Different Nozzle Exit Positions - Zhang Xiping; Deng Jianqiang; Li Yafei; He Yang (Zhileng xuebao)
The ejector is one of the key components of a transcritical CO2 ejector expansion refrigeration system, and the nozzle exit position (NXP) is the main geometric parameter. Therefore, research on the structure, performance, and internal flow mechanism of the ejector is beneficial for improving the performance of the ejector system. In this study, a visualization ejector with different NXPs was designed and manufactured. The entrainment ratio and pressure recovery ratio of the CO2 two-phase ejector with different NXPs were obtained in a transcritical CO2 ejector expansion refrigeration system. Furthermore, the pressure distribution along the primary nozzle, mixing section, and diffuser section was measured using a pressure sensor. Simultaneously, the expansion angle, expansion length, and phase change position of the primary flow were captured using a high-speed camera. According to the experimental results, the performance of the ejector is influenced by the expansion profile. Specifically, the short NXP (4 mm) led to a short expansion length, large expansion angle, and high-pressure recovery ratio, but the corresponding entrainment ratio was relatively low. As the NXP increased to 6 mm and 8 mm, the expansion of the primary flow was more sufficient, the expansion length was longer, the expansion angle was smaller, and the entrainment ratio was improved. A further increase in the nozzle distance to 10 mm contributed to a larger expansion angle as well as a low entrainment ratio and pressure recovery ratio. From the results, the optimal NXP is in the range of 6–8 mm for the ejector under the operating conditions of this study. The results of this study contribute to a better understanding of the internal flow mechanism of the ejector and help to improve its design theory.